A Monitoring Framework for Global Financial Stability - Adrian, Tobias (Staff Discussion Notes; Staff Discussion Notes ;, 2019)
This paper describes the conceptual framework that guides assessments of financial stability risks for multilateral surveillance, as currently presented in the Global Financial Stability Report (GFSR). The framework emphasizes consistency in measuring financial vulnerabilities across countries and over time and offers a summary statistic to quantify aggregate financial stability risks. The two parts of the empirical approach-a matrix of specific vulnerabilities and a summary measure of financial stability risks-are distinct but highly complementary for monitoring and policymaking.